FAKTOR RISIKO TERJADINYA HIPERTENSI PADA USIA DEWASA - Firmansyah, Firmansyah; Yunianti, Yuli; Rinjani, El Zenitia Villa; Alfira, Jihan (Ensiklopedia of Journal, 2025)
Abstract: Hypertension is a medical condition characterized by persistently elevated blood pressure, where systolic pressure reaches or exceeds 140 mmHg and diastolic pressure reaches or exceeds 90 mmHg. The aim of this study was to identify risk factors for hypertension in adults. The study design used in this research was cross-sectional. The study was conducted in the working area of the Sinjai Community Health Center in April 2024. The population in this study consisted of 1,865 hypertensive patients who had visited the Manipi Community Health Center in West Sinjai District. The sample size was 95 people. The sampling technique used was purposive sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results of the study indicate a relationship between sleep quality (p-value: 0.03) and sleep quality (p-value: 0.00) with the occurrence of hypertension. It is recommended that health centers provide counseling to patients regarding factors that influence the occurrence of hypertension, particularly obesity and stress, and teach families to assist patients in preventing hypertension, especially in maintaining nutrition and managing stress.Keywords: Hypertension, Sleep Quality, Stress.